EVALUASI PENERAPAN PSAK 34 DI PT. PARAMITA BANGUN SARANA, TBK (Media Riset Akuntansi, 2022)
This study aims to analyze whether the accounting treatment of measurement, recording, presentation and disclosure of construction service revenues at PT. Paramita Bangun Sarana, Tbk has complied with PSAK 34. The research method used in this research is descriptive qualitative method. The result of this research is that the accounting treatment in measuring, recording, and disclosing the revenue of construction services of PT. Paramita Bangun Sarana, Tbk has complied with PSAK 34 but for the recognition and presentation of revenue it is not in accordance with PSAK 34 because it does not present actual revenue.